Pemanfaatan Eceng Gondok Terhadap Penurunan Kadar Merkuri (Hg) Limbah Cair Pada Pertambangan Emas Tanpa Izin (PETI) The Use of Eichornia Crassipes to Reduce Mercury (Hg) Levels on Liquid Waste in Illegal Gold Mines - Shelga Sapta Lahenda; Ellyke Ellyke; Khoiron Khoiron (Pustaka Kesehatan, 2015)
Nowadays emerge event about global worried will have negative effect from highereconomic development to our environment that causes to develop of industry, one ofthem is Illegal Gold Mines industry. This industry very close with environment problembecause it outcomes is waste that consists of high metal, one of them contains mercury(Hg). The preliminary study was done in village sumberagung, pesanggaran,banyuwangi by first Hg value is 0,038 mg/L over environment quality reciprocal. Thealternative of waste processing was by using Eichornia crassipes. The purpose of thisresearch to know the differences of liquid waste Hg value before and after usingEichornia crassipes. This reserach experimental with True Eksperimental Design. Thisresearch have control group with treatment as reserach independent variable. Controlgroup is a group without using Eichornia crassipes, first group (X1) is a group that usingEichornia crassipes with weight 300 gr/L, second group (X2) is a group that usingEichornia crassipes with weight 400 gr/L, third group (X3) is a group that using Eichorniacrassipes with weight 500 gr/L. Analysis of the data using one way anova test. Thisresearch result with signifikasi 0,05, there is significant differences between that fourthexperiment group. The most effective to reduce Hg value is the third group treatment(X3) by using hyacinth with weight 500 gr/L.Keywords : Illegal Gold Mines, Eichornia crassipes, Mercury (Hg)